Characteristics of patients with idiopathic normal pressure hydrocephalus for whom neurosurgeons hesitate to perform shunt surgery: a nationwide hospital-based survey in Japan - Ryo Kawai; Hiroaki Kazui; Tetsuya Ueba; Natsuko Nakamura; Marina Minami; Madoka Nakajima; Shigeki Yamada; Haruhiko Kishima; Hideki Kanemoto; Chifumi Iseki; Etsuro Mori (Fluids and Barriers of the CNS)
Abstract Background There is no consensus regarding the indications for shunt surgery in patients with idiopathic normal pressure hydrocephalus (iNPH) aged ≥ 85 years or in those with severe physical or mental comorbidities. This nationwide study investigates the current approaches of neurosurgeons regarding iNPH treatment and surgical indications. Methods A questionnaire, developed in collaboration with neurosurgeons and dementia specialists, was distributed to 1,220 facilities from October 10, 2023. Responses were collected through December 11, 2023 and analyzed to assess current practices and factors influencing surgical decisions. Results In total, 656 facilities (53.8%) responded. Of them, 30 (4.6%) had a policy of not performing shunt surgery at their own facility and referred patients to other appropriate facilities, and 139 (21.2%) did not perform any shunt surgeries in 2022. The most common number of shunt surgeries performed in 2022 was 1–5 surgeries per facility, accounting for 257 facilities (57.1%). Regarding age-related indications for shunt surgery, 159 facilities (35.3%) reported no age restrictions, whereas 155 facilities (57.8%) among the 268 facilities considering age (59.6%) responded that patients aged ≥ 90 years were not indicated for shunt surgery. Among 450 facilities that performed shunt surgeries in 2022, hesitations resulting from comorbidities were reported as follows: cerebrovascular disease (10.0%), orthopedic disease (11.5%), dialysis (29.8%), Parkinson’s syndrome (19.5%), Alzheimer’s disease (AD) (42.7%), schizophrenia (44.2%), absence of disproportionately enlarged subarachnoid space hydrocephalus (DESH) (41.5%), and insufficient care or institutionalization (56.0%). Logistic regression analyses showed that the number of shunt surgeries performed in 2022 was significant predictor of age ≥ 90 years, cerebrovascular disease, Parkinson’s syndrome, AD, no DESH, and insufficient care or institutionalization. Significant predictors for dialysis, AD, and schizophrenia included the presence of collaborating internal medicine facilities. For dialysis and AD, the classification of facilities and having a qualified dementia specialist were significant predictors, respectively. Conclusions A number of Japanese neurosurgeons hesitate to perform shunt surgery in patients with iNPH aged ≥ 90 years, with comorbid AD or schizophrenia, lacking DESH findings, or having insufficient care support or are institutionalized. Multidisciplinary collaboration with internal medicine, including neurology and psychiatry, may help expand appropriate surgical indications for these patients.